1986
DOI: 10.1007/bf00172866
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the memory of a previously learned aversive habit following pre-test administration of a variety of serotonergic antagonists in mice

Abstract: The present study examined the effects of pre-test administration of a number of serotonergic receptor antagonists on the retrieval of a previously learned aversive habit in the mouse. All of the receptor antagonists (pirenperone, ketanserin, mianserin, methysergide and metergoline) produced a dose-dependent increase in the latency to complete 5 s of drinking 48 h after training. This suppression of drinking could not be attributed to nonspecific effects of the drugs on behavior (e.g., illness, reduced thirst,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(15 citation statements)
references
References 31 publications
1
13
0
1
Order By: Relevance
“…The results of the present study suggest for the first time that blockade of serotonin receptors (5-HTJ shortly before retention testing can enhance retrieval of a previously learned aversive habit. The results of the present study are also consistent with the fact that serotonergic system has inhibitory influence on learning and memory (Altman & Normile 1986). Some previous reports have shown that stimulation/enhancement of serotonin activity impairs learning (Garzon et al 1981;Fibiger et af.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of the present study suggest for the first time that blockade of serotonin receptors (5-HTJ shortly before retention testing can enhance retrieval of a previously learned aversive habit. The results of the present study are also consistent with the fact that serotonergic system has inhibitory influence on learning and memory (Altman & Normile 1986). Some previous reports have shown that stimulation/enhancement of serotonin activity impairs learning (Garzon et al 1981;Fibiger et af.…”
Section: Discussionsupporting
confidence: 92%
“…It is likely that effects of 5-HT are mediated through different 5-HT receptor subtypes (Peroutka 1984). Altman & Normile (1986) using a variety of 5-HT antagonists have shown an enhancement of memory in a passive avoidance task. However, Jones et al (1990) and Costall et al (1 989) could not show any per se effects of 5-HT3 antagonists (i.e.…”
mentioning
confidence: 99%
“…These findings contrast with the lack of effect of tryptophan depletion on SWM (Park et al 1994) and normal performance of depressive patients on this task (Purcell et al 1997). However, animal studies do provide evidence of improved working memory function in 5-HTdepleted conditions (Altman and Normile 1986;Fontana et al 1995). Administration of the 5-HT-releasing agent fenfluramine was reported to impair SWM processes of healthy volunteers (Luciana et al 1998).…”
Section: Discussionmentioning
confidence: 81%
“…Animal research has shown decreased sensitivity to outcome-devaluation as a result of serotonin receptor antagonism, or serotonin depletion (Altman and Normile, 1986; Clarke et al, 2007). Furthermore, a recent study investigating tryptophan (a precursor to serotonin) depletion in humans suggested this promoted a reliance on habits in the Slips-of-Action paradigm (Worbe et al, 2015), and so an effect of serotonergic medication cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%